Fungicides With Contrasting Mode of Action Differentially Affect Hyphal Healing Mechanism in Gigaspora sp. and Rhizophagus irregularis - Rodriguez-Morelos, Victor Hugo; Calonne-Salmon, Maryline; Bremhorst, Vincent; Garcés-Ruiz, Mónica; Declerck, Stéphane (Frontiers in Plant Science, 2021)
Fungicides are widely used in conventional agriculture to control fungal diseases, but may also affect non-target microorganisms such as arbuscular mycorrhizal (AM) fungi. These root symbionts develop extended mycelial networks within the soil via mechanisms such as anastomosis that indistinctly concerns intact and damaged hyphae, the latter being named hyphal healing mechanism (HHM). The HHM differs between Glomeraceae and Gigasporaceae. However, the effects of fungicides on this mechanism in unknown. Here, the impact of azoxystrobin, pencycuron, flutolanil and fenpropimorph at 0.02 and 2 mg L−1 were tested in vitro on the HHM of Gigaspora sp. MUCL 52331 and Rhizophagus irregularis MUCL 41833, and repair events visualized carefully under a dissecting bright-field light microscope. Azoxystrobin was the more detrimental for both AM fungi at 2 mg L−1, while fenpropimorph impacted only R. irregularis (stimulating at low and inhibiting at high concentration). Conversely, flutolanil and pencycuron did not impact any of the two AMF fungi. The mechanisms involved remains to be elucidated, but perturbation in the still-to-be firmly demonstrated spitzenkörper or in sterols content as well as a process of hormesis are possible avenues that deserve to be explored in view of a rationale management of chemicals to control fungal pathogens without harming the beneficial AM fungi.